2010
DOI: 10.1177/0265407510384897
|View full text |Cite
|
Sign up to set email alerts
|

‘‘We’re not living together:’’ Stayover relationships among college-educated emerging adults

Abstract: Rapid and widespread changes in relationship formation and dissolution over the past 50 years have revealed new patterns in romantic and sexual relationships, particularly among emerging adults. In this study, grounded theory methods were used to investigate the role of one such pattern, stayovers, in the development of romantic relationships among 22 college students and college graduates. The results indicated that some young couples stay overnight between three and seven nights per week while living in sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…Among those with a high school degree or post-secondary schooling but no Bachelor’s degree, half began cohabiting within six months of the relationships start. The college educated, in contrast, were romantically and sexually involved for longer periods (on average a year) before moving into shared living (Sassler and Miller 2011), consistent with Jamison and Ganong (2011). Highly educated couples also more frequently reported concrete marriage plans than their less educated counterparts, suggesting that their transition from cohabitation into marriage occurred more rapidly (Sassler and Miller 2011, 2017).…”
Section: Research On the Tempo Of Relationship Progressionmentioning
confidence: 96%
See 2 more Smart Citations
“…Among those with a high school degree or post-secondary schooling but no Bachelor’s degree, half began cohabiting within six months of the relationships start. The college educated, in contrast, were romantically and sexually involved for longer periods (on average a year) before moving into shared living (Sassler and Miller 2011), consistent with Jamison and Ganong (2011). Highly educated couples also more frequently reported concrete marriage plans than their less educated counterparts, suggesting that their transition from cohabitation into marriage occurred more rapidly (Sassler and Miller 2011, 2017).…”
Section: Research On the Tempo Of Relationship Progressionmentioning
confidence: 96%
“…Several studies suggest that entry into cohabitation occurs gradually. Jamison and Ganong (2011) interviewed college-educated daters ( n = 22), and described how respondents gradually began spending nights together over time (stayovers, in their terminology), progressively increasing the number of nights. Manning and Smock (2005) drew on interviews with a diverse sample of 115 young adults with current and past cohabitation experience, and found that couples reported spending more and more nights together with increasing relationship duration.…”
Section: Research On the Tempo Of Relationship Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many young people, LAT is a stage in the union formation process, preceding cohabitation and/or marriage (Liefbroer et al, 2015;Strohm et al, 2009). They may not be ready for the perceived greater commitment associated with co-residence (Jamison & Ganong, 2011). Older adults may choose not to live with their partner because they are responsible for taking care of children or elderly parents with whom they live in the same household (Levin & Trost, 1999).…”
Section: Previous Literaturementioning
confidence: 99%
“…An alternative to cohabitation common in emerging adults is known as "stayover relationships" (Jamison and Ganong 2011). "Stay-over relationships" consist of a couple spending the night at one another's residence anywhere between three and seven times a week.…”
Section: Changes In Mentality Of Datingmentioning
confidence: 99%